PEREMPUAN DAN PERHIASAN EMAS: SIMBOL KEJAYAAN LAKI-LAKI MADURA DI DESA BINOH KECAMATAN BURNEH KABUPATEN BANGKALAN - Rialda Safitri Agustina; Sarmini (Kajian Moral dan Kewarganegaraan, 2026)
One of the symbols of dignity and glory for Madurese men is reflected in women through their gold jewelry. Many Madurese women wear gold jewelry in large quantities and sizes, this has even become a social phenomenon. This study aims to describe the perspectives of Madurese men and women regarding gold jewelry as a symbol of men’s glory, as well as to identify the elements that influence these perspectives. The theoretical framework used is Alfred Schutz’s Phenomenological Theory. This research employs a qualitative method with a phenomenological approach. Data were collected through in-depth interviews and participant observation. Data analysis is conducted using Moustakas’ phenomenological analysis. The findings of this study indicate that: (1) Gold jewelry is similarly interpreted by both Madurese men and women as a symbol of success. However, men tend to view gold jewelry as a symbol of dignity, pride, affection, and responsibility toward the family, while women interpret it as a symbol of beauty, honor, and self-identity; (2) The perspectives of Madurese men and women are influenced by elements such as knowledge, culture and tradition, and the social environment; (3) These perspectives on gold jewelry emerge from both because motives (experiences and inherited values related to honor and status) and in-order-to motives (the desire to maintain social image in the present as well as future-oriented aspirations); (4) Gold jewelry is not merely material in value as an investment or savings, but also carries social, cultural, and moral meanings related to perceptions of honor and gender roles (husband-wife).